A new species of Discothyrea Roger (Hymenoptera: Formicidae) from the Brazilian Atlantic Rainforest - Chaul, Júlio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
A new species of the cosmopolitan genus Discothyrea Roger, a member of the Proceratiinae subfamily, is described for the Brazilian Atlantic Forest. The species, Discothyrea bobi sp. nov., is compared to the other New World species described for the genus so far. Two putatively important morphological features of the genus, the palpal formula and the antennal pits, are discussed.